DOPS, a cidade de Rolândia (PR) e a repressão aos imigrantes de origem alemã (1942-1945) - Priori, Angelo; Ipólito, Verônica Karina [UNESP] (Pós-Graduação em História, Faculdade de Filosofia e Ciências Humanas, Universidade Federal de Minas Gerais, 2015)
The activities by the political police (DOPS) against German immigrants in Rolândia PR Brazil between 1942 and 1945 are discussed. The alliance of Brazil with the Allies during the II World War triggered the control and monitoring of immigrants from the Axis countries by the political police of the Vargas administration. The constant reference to Germans constructed a series of myths, such as ‘the German Conspiracy’ and ‘Antarctic German’ that legitimized the ‘logics of suspicion’ on the immigrants. The construction of political myths foregrounded in the social imaginary the actions of political police and legalized their control and persecution activities.

O artigo analisa as ações realizadas pela Delegacia de Ordem Política e Social (DOPS) contra os imigrantes alemães, na cidade de Rolândia/PR, no período de 1942 a 1945. Durante a II Guerra Mundial e a adesão do Brasil aos países Aliados, os imigrantes dos países do Eixo foram vigiados e controlados pela polícia política do governo Vargas. A constante referência aos alemães acabou gerando a construção de mitos, como o da “conspiração alemã” e o da “Alemanha Antártica”, que ajudaram a legitimar a “lógica da desconfiança” sobre esses imigrantes. A construção de mitos políticos respaldou, no imaginário social, a atuação da polícia política, legitimando as suas ações de vigilância, controle e repressão.
DOPS, Rolândia and the Persecution of German Immigrants (1942-1945)
Keywords: Political Police; Social Control; Repression; German Immigration; Polícia Política; Controle Social, Repressão; Imigração Alemã